Synthesis and Antimicrobial Evaluation of Some Bis-1, 3, 4-Butane-1-3, 4-Oxadiazole Derivatives - Omar–Eldeen, H.I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A series of new Bis-1,4-Butane -1,3,4 – Oxadizole derivatives [III a-j] were synthesized from adipic acid dihydrazide and different aromatic acids in the presence of phosphours oxychloide. There compounds were characterized by their IR, microanalysis, and mass spectral data. In vitro antimicrobial were synthesized. In vitro antimicrobial activity of these compounds against (Gram negative) and (Gram positive) were reported, some of these compounds prepared derivatives exhibited antimicrobial activity